Pembuatan Kemasan Produk Ikan Asap sebagai Strategi Promosi Produk di Desa Suradadi, Tegal - Ike Desi Florina; Sri Mulyani; Itsna Hidayatul Khusna (Universitas Mathla'ul Anwar Banten, 2019)
MAKING SMOKED FISH PRODUCT PACKAGING IN SURADADI VILLAGE AS A PRODUCT PROMOTION STRATEGY. Promotion is the common problem for micro enterpreneur/start up to increase product selling. This problem has been problem for smoked fish producer in Suradadi Village, Tegal Regency. To resolve these problems, we as service society team made an action along with smoked fish producer as partner. In this activities we used several methodes that is socialization, building renovation, packaging, and promoting. The socialization was consist of promotion strategy socialization, and training in the use of social media. Renovation is done by replacing defective building, organizing and cleaning the place which located for place of business. Next is to make product packaging, so that the product looks more attractive to buy. Promotion activities was utilize social media for product promotion, and install signpost near roadway to point business place. The results achieved from this partnership activity are an increase in buyer knowledge of smoked fish products, and an increase in the number of buyers with the promotion of social media and the installation of signposts.